Pertanggung Jawaban Hukum Terhadap Kenyamanan Konsumen Dalam Pertunjukan Film di Bioskop Ditinjau dari Undang-Undang Perlindungan Konsumen - Laka, Merenggang Tegung; Tobing, Padimun Lumban (Neolectura, 2025)
Consumer comfort in the cinema experience is a right that cinema operators must uphold according to the Consumer Protection Law (UUPK) No. 8 of 1999. This study examines the legal responsibilities of cinema operators to ensure consumer comfort, including the quality of facilities, accurate information, and complaint mechanisms. A normative juridical research method is used, referencing the UUPK regulations as well as Law No. 33 of 2009 on Film. The study finds that consumer discomfort, such as inadequate facilities or misleading information, can result in consumer rights to seek legal accountability through complaints and compensation as outlined in Article 19 of the UUPK. Furthermore, the complaint mechanism through the Consumer Dispute Settlement Body (BPSK) functions to facilitate swift and efficient resolution of issues experienced by consumers. This study aims to serve as a reference for cinema operators to improve services and understand the legal consequences of unfulfilled obligations, while also educating consumers on their rights within the scope of film service provisions.